The Role of Management Control Systems in Enhancing Business Strategy Effectiveness and Innovation: Implications for Company Performance - Fazri, Edward; Muttaqin, Galih Fajar; Bagaskara, Kurniarga (PT. EQUATOR SINAR AKADEMIA, 2024)
This study investigates the role of Management Control Systems (MCS) in supporting business strategy effectiveness and innovation, and how these factors influence company performance within the financial services sector. Using a quantitative approach, data were collected through structured questionnaires distributed to 150 financial service companies in Indonesia. The analysis, performed using Partial Least Squares Structural Equation Modeling (PLS-SEM), indicates that MCS positively influences both business strategy effectiveness and innovation. Additionally, the findings reveal that both business strategy effectiveness and innovation significantly contribute to improved company performance. These results underscore the importance of MCS as a strategic tool for fostering innovation and aligning business strategies, ensuring that organizations can navigate dynamic market environments effectively. The study offers practical insights for managers in financial services, emphasizing the need to leverage MCS not only for operational oversight but also as a facilitator of strategic alignment and innovation. Future research may explore these dynamics across different sectors and regions to further validate these findings.